MRN- and 9-1-1-Independent Activation of the ATR-Chk1 Pathway during the Induction of the Virulence Program in the Phytopathogen Ustilago maydis - Tenorio-Gómez, María; de Sena-Tomás, Carmen; Pérez-Martín, Jose (PLOS ONE, 2015)
DNA damage response (DDR) leads to DNA repair, and depending on the extent of the damage, to further events, including cell death. Evidence suggests that cell differentiation may also be a consequence of the DDR. During the formation of the infective hypha in the phytopathogenic fungus Ustilago maydis, two DDR kinases, Atr1 and Chk1, are required to induce a G2 cell cycle arrest, which in turn is essential to display the virulence program. However, the triggering factor of DDR in this process has remained elusive. In this report we provide data suggesting that no DNA damage is associated with the activation of the DDR during the formation of the infective filament in U. maydis. We have analyzed bulk DNA replication during the formation of the infective filament, and we found no signs of impaired DNA replication. Furthermore, using RPA-GFP fusion as a surrogate marker of the presence of DNA damage, we were unable to detect any sign of DNA damage at the cellular level. In addition, neither MRN nor 9-1-1 complexes, both instrumental to transmit the DNA damage signal, are required for the induction of the above mentioned cell cycle arrest, as well as for virulence. In contrast, we have found that the claspin-like protein Mrc1, which in other systems serves as scaffold for Atr1 and Chk1, was required for both processes. We discuss possible alternative ways to trigger the DDR, independent of DNA damage, in U. maydis during virulence program activation.